Comparative Analysis of HAND with TWI Flood-Prone Mapping Models in Data-Scarce Areas - Purwanto, Ajun; Andrasmoro, Dony; Eviliyanto, Eviliyanto (Faculty of Geography, Universitas Gadjah Mada, 2025)
Flood is one of the most frequent natural disasters in Indonesia and worldwide. Therefore, this study aimed to compare and evaluate flood-prone mapping model using Height Above Nearest Drainage (HAND) and Topographic Wetness Index (TWI) model in data-scarce areas. HAND and TWI models were used to estimate flood-prone level, with field survey and image interpretation as primary methodologies. The data used was Digital Elevation Model (DEM) imagery with a resolution of 10 meters, incorporating elevation, slope, and hydrological parameters namely flow accumulation, direction, and distance. The mapping flood-prone areas were categorized as very prone, prone, moderate, not prone, and very not prone. The results showed that there were differences between HAND and TWI models in terms of area and percentage. The differences in flood inundation characteristics produced by HAND model were mainly due to variations in elevation and proximity to drainage channels. In contrast, TWI model focused on topography, soil moisture, and runoff potential. The differences between the two models also emphasized the importance of terrain characteristics in model predictions. The comparable predictive ability of HAND and TWI models presents an alterReceived: 2024-08-15 Revised: 2 024-09-12Accepted: 2025-03-22 Published: 2025-05-26